Making biodiversity their business - Hamilton, Hannah Elizabeth (Trinity College Dublin. School of Natural Sciences. Discipline of Botany, 2021)
Biodiversity loss has emerged as a threat to humanity equal to that of climate change. Urgently addressing this loss requires transformational change across many sectors of society. Global studies have highlighted the significance of the private sector?s role in driving biodiversity loss and the importance of transformational systems change in harnessing the power of business to support biodiversity conservation targets and objectives. However, little research has been done to explore the connections between business and biodiversity, and even less has been done to understand the business case for action. This research project seeks to address a specific aspect of that gap. It focusses on a multi-sectoral group of companies that have undertaken a voluntary certification scheme ? the Biodiversity Benchmark ? to assess their on-site biodiversity management systems. The scheme is administered across the United Kingdom by The Wildlife Trusts, a well-known conservation charity. To understand the business drivers, benefits and barriers to engagement with this scheme, I first conducted a small-scale exploratory study to gather empirical data on employees? perceptions. I took a mixed methods approach to first identifying potential drivers, benefits and barriers through semi-structured interviews with The Wildlife Trusts? Biodiversity Benchmark assessors. The findings were then translated into an online survey that was circulated to a wider group of employees at the participating companies. Lastly, the survey findings were further explored through semi-structured interviews with a subset of the survey respondents. Survey and interview findings were then synthesised and discussed to establish the cross-sectoral drivers, benefits and barriers of business engagement with voluntary on-site biodiversity management within the sample. I found that a passionate individual with a personal interest in biodiversity was thought to be an important driver of business engagement. I also found that doing the right thing ? both in terms of corporate responsibility and an effective approach based on embedding biodiversity in management systems to ensure continual improvement ? apparently drove engagement, as did the recognition and validation of efforts by a trusted third party (in this case, a well-known environmental charity). The perceived business benefits of undertaking the scheme included: an enhanced reputation among and better relationships with local communities and regulators; the management of risk in terms of access to licences and permissions and compliance with legislation and conditions; improved employee engagement ? especially in terms of health and wellbeing, staff morale and a sense of pride; and benefits around businesses being seen as leaders by external stakeholders for striving for best practice. Combined, my analysis of responses suggests that a passionate and highly motivated employee together with an enabling corporate culture and a business-relevant management framework can drive positive outcomes for biodiversity, employee engagement, business reputation, community relationships and risk management. Further research is needed to interrogate these findings in larger samples and to explore similar questions in other areas of business action on biodiversity, especially through inter-disciplinary studies that investigate the business perspective. Business impacts and dependencies on nature are widely discussed in conservation science but, while there are signs of increased engagement, the implications of biodiversity loss generally remain poorly understood in the private sector. In the context of evermore ambitious policy goals for biodiversity and increasingly stringent environmental legislation, there is an urgent need to develop the business case for biodiversity and support broad cross-sectoral action through the development of tools, methodologies and approaches that businesses value.
A mixed methods analysis of stakeholder perceptions on the business drivers, benefits and barriers of a corporate biodiversity certification scheme
APPROVED
Keywords: Biodiversity; Corporate responsibility; Sustainability; Nature conservation; Business